Natural Coating from VG2S in Reducing Surface Temperature. - Abidin, AHZ; Omar, RC; Roslan, R; Taha, Hairin; Sanusi, KA (International Journal of Engineering and Technology, 2018)
Urban heat island (UHI) is a condition where urban area experiences increase in temperature than rural area caused by the affect from the modification of land surfaces. In urban areas, roads are one of the main elements that contribute to UHI as roads are mostly paved with dark pavement. When pavements become hotter, the excess heat is radiated back into the atmosphere resulting in a higher surrounding temperature than those in rural areas. The objective of this study is to develop a new coating material for pavers from VG2S that can reduce surface heat. Two methods were used in this study, immersed and layered methods for comparing standard paver with new innovated paver with VG2S coating. FLIR thermal imaging camera and infrared thermometer gun are used for measuring surface heat. The surface heat result shows reduction in surface temperature by 5°C to 10°C compared to uncoated standard sample and white paint color pave sample (control) which are slightly lower by 1°C to 2°C from coating sample. The studies demonstrated that VG2S coating can be applied as cool coatings and contribute to a significant reduction of the cooling demand in warm climates.